FATORES QUE INFLUENCIAM NA IMPLANTAÇÃO DA GESTÃO DE PROCESSOS: UM ESTUDO DE CASO MÚLTIPLO - Horovitz, Flávio (2012)
This work identifies the factors, and their influence, in BPM implementation initiatives results. Initially, a bibliographic review was conducted defining the factors to be analyzed in a research involving twenty two professionals from two business consulting companies which have worked in three BPM implementation projects conducted in Brazilian companies. The research responses were processed using descriptive statistics tools, and analyzed aiming to understand, from the respondents perspective, which are the most relevant factors. Results highlights: eight of ten most relevant factors relate do the processes conception phase; technology area must act as a BPM implementation initiative partner; processes managers and executors must validate the future processes designs. People, technology and processes are extremely relevant for the BPM implementation initiative success.